Novye pochody k ponimaniju sportivnych stressovych immunodefizitov - Suzdalnitskij, R. S.; Levando, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
Immunology - one of most roughly developing sciences of our time. The second half of the 20th century they name the century of biology and it is obliged to it by the development of immunology. Nobody counted up, how many diseases have in its basis unbalanced immune system. The authors believe, that practically in everything, except for traumas with lethal end and some endocrines diseases where there is the failure at the genetic level. Scientists of all biological specialties consider immune system today as the universal receptive body which distinguishes and sorts external and internal antigenic signals of a different nature, transfers the significant information on volume both on nervous fibers, and through blood flow in strategically rationally located bodies of immunity, using numerous combinations of cellular and humoral factors with participation of hormones. The imperative need in classification of the immune deficiency conditions at athletes, which authors represent in the article, has ripened today.